Circulating β cell-specific CD8+ T cells restricted by high-risk HLA class I molecules show antigen experience in children with and at risk of type 1 diabetes - L. Yeo; I. Pujol-Autonell; R. Baptista; M. Eichmann; D. Kronenberg-Versteeg; S. Heck; G. Dolton; A. K. Sewell; T. Härkönen; M.-L. Mikk; J. Toppari; R. Veijola; et al. (Blackwell Publishing Ltd, 2022)
In type 1 diabetes (T1D), autoreactive cytotoxic CD8+ T cells are implicated in the destruction of insulin‐producing β cells. The HLA‐B*3906 and HLA‐A*2402 class I genes confer increased risk and promote early disease onset, suggesting that CD8+ T cells that recognize peptides presented by these class I molecules on pancreatic β cells play a pivotal role in the autoimmune response. We examined the frequency and phenotype of circulating preproinsulin (PPI)‐specific and insulin B (InsB)‐specific CD8+ T cells in HLA‐B*3906+ children newly diagnosed with T1D and in high‐risk HLA‐A*2402+ children before the appearance of disease‐specific autoantibodies and before diagnosis of T1D. Antigen‐specific CD8+ T cells were detected using human leucocyte antigen (HLA) class I tetramers and flow cytometry was used to assess memory status. In HLA‐B*3906+ children with T1D, we observed an increase in PPI5–12‐specific transitional memory CD8+ T cells compared to non‐diabetic, age‐ and HLA‐matched subjects. Furthermore, PPI5–12‐specific CD8+ T cells in HLA‐B*3906+ children with T1D showed a significantly more antigen‐experienced phenotype compared to polyclonal CD8+ T cells. In longitudinal samples from high‐risk HLA‐A*2402+ children, the percentage of terminal effector cells within the InsB15–24‐specific CD8+ T cells was increased before diagnosis relative to samples taken before the appearance of autoantibodies. This is the first study, to our knowledge, to report HLA‐B*3906‐restricted autoreactive CD8+ T cells in T1D. Collectively, our results provide evidence that β cell‐reactive CD8+ T cells restricted by disease‐associated HLA class I molecules display an antigen‐experienced phenotype and acquire enhanced effector function during the period leading to clinical diagnosis, implicating these cells in driving disease.